DETECTION OF JAPANESE ENCEPHALITIS VIRUS AND HERPES SIMPLEX VIRUS IN AES CASES BY ELISA AND PCR IN A TERTIARY CARE HOSPITAL OF EASTERN INDIA - Kumar Rout, Manish; Projna Paty, Bimoch; Dwibedi, Bhagirathi; Chayani, Nirupama (International Journal of Clinical and Biomedical Research, 2017)
Encephalitis is defined as inflammation of the brain parenchyma associated with neurologic dysfunction. AES occurs in explosive epidemics or in a non-epidemic (sporadic) form. Epidemic in India have been attributed to Japanese encephalitis virus (JEV) infection. Herpes simplex virus (HSV) is responsible for most sporadic cases of AES. This study was undertaken to detect JEV and HSV from CSF samples. Method: Two to three ml of CSF was collected in a dry sterile container. Samples were divided into 2 vials and kept at -20oC. One vial was used for ELISA test in while the other vial was used for PCR. Result: Of 90 cases, 61 were males (68%), 29 were females (32%). Majority belonged to 1 month-5years in 34 (38%) cases followed by 6-10 years in 23 (26%) cases. The commonest symptom was fever in 90 (100%) cases followed by change in mental status in 86 (95.6%).Of 90 samples 2 (2.2%) was positive for JEV in PCR while only 1 (1.1%) was positive in ELISA. A total of 9 (10%) samples were positive for HSV 1 & 2, of which 8 (8.9%) samples were positive in ELISA assay and 8 (8.9%) were positive in PCR assay. In our study only 2 (2.2%) samples were positive for JEV in PCR while one was negative in ELISA. 9 (10%) samples were tested positive for HSV which signifies the sporadic nature of the virus in this region. Conclusion: PCR was found to be more sensitive in detection of JEV, while in HSV detection both ELISA and PCR were equally sensitive. Key words: Japanese B encephalitis virus; Herpes simplex virus; Acute encephalitis syndrome; Polymerase chain reaction; Enzyme linked immunosorbent assay.